Effects of cartilage acellular solubilised ECM on physicomechanical and biological properties of polycaprolactone/fibrin hybrid scaffold fabricated by 3D-printing and salt-leaching methods. (23rd February 2022) - Honarvar, Ali; Karbasi, Saeed; Hashemibeni, Batool; Setayeshmehr, Mohsen; Kazemi, Mohammad; Valiani, Ali
ABSTRACT: Scaffold fabrication methods have a vital role in cartilage tissue engineering (CTE). For a long time, extracellular matrix (ECM) derivatives have been used to improve chondrogenesis and cartilage regeneration. In this study, polycaprolactone (PCL) scaffolds were prepared by 3D-printing and salt-leaching methods. Then, the prepared scaffolds were coated with fibrin and different acellular solubilised ECM concentrations. Adipose-derived stem cells (ADSCs) were added to fibrin/ECM hydrogel and seeded on the PCL scaffolds. Results showed that water absorption and compressive moduli of the 3D-printed scaffolds were higher than salt-leached scaffolds. As ECM was added and concentration increased, porosity was decreased and water uptake increased significantly. 3D-printed scaffolds with ECM2% group demonstrated a high compressive modulus and cell viability. Therefore, we concluded 2% is the most suitable concentration for acellular solubilised ECM in order to fabricate more biocompatible and applicable PCL/fibrin/ECM scaffolds in CTE.